How Does Vaccination against SARS-CoV-2 Affect Hospitalized Patients with COVID-19? - Moreno-Nuñez, Paloma; Bueno-Cavanillas, Aurora; San José Saras, Diego; Vicente-Guijarro, Jorge; Fernández Chávez, Abelardo; Aranaz Andrés, Jesús María (Journal of Clinical Medicine, 2023)
Background: The development of effective COVID-19 vaccines has reduced the impact of COVID-19 on the general population. Our study aims to analyze how vaccination modifies the likelihood of death and length of stay in hospitalized patients with COVID-19; (2) Methods: A retrospective cohort study of 1927 hospitalized patients infected with COVID-19 was conducted. Information was gathered on vaccination status, hospitalization episode, and clinical profile of the patients. The effect of vaccination on mortality was analyzed using a multiple logistic regression model, and length of stay was analyzed using linear regression. The performance and fit of the models were evaluated; (3) Results: In hospitalized patients with COVID-19, the risk of dying during admission in vaccinated patients was half that of non-vaccinated (OR: 0.45; CI 95%: 0.25 to 0.84). In patients who were discharged due to improvement, the reduction in hospital stay in vaccinated patients was 3.17 days (CI 95%: 5.88 to 0.47); (4) Conclusions: Patients who, despite having been vaccinated, acquire the infection by SARS-CoV-2, have a significant reduction of the risk of death during admission and a reduction of hospital stay compared with unvaccinated patients.
Keywords: COVID-19; vaccinesvaccine effectiveness; hospital mortality; critical care; hospitalisation; JCR; Scopus